Hegemoni Kerajaan Hiburan Disney - Fitrinanda An Nur (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
Disney is a huge giant company through its power to embrace its audience. The company is increasingly developing various types of businesses including businesses outside of its film work. Children are Disney's main target in the development of this business. This paper aims to see the business development of The Walt Disney Company in the perspective of the political economy of communication by using one of the entrances, namely spatialization. Business development carried out by Disney is through vertical and horizontal integration. Disneyini's business development is supported by globalization and technology, so that Disney can reach its target market by removing boundaries between time and space.